Midbrain Dopamine Neurons Defined by TrpV1 Modulate Psychomotor Behavior - Serra, Gian Pietro; Guillaumin, Adriane; Dumas, Sylvie; Vlcek, Bianca; Wallén-Mackenzie, Åsa (Frontiers in Neural Circuits, 2021)
Dopamine (DA) neurons of the ventral tegmental area (VTA) have recently gained attention as more heterogeneous than previously believed. One recent advance has been the demonstration that molecular profiles differ between DA neurons, a feature which allows their separation into molecularly distinct subtypes. Another realization is that some DA neurons possess the capacity for glutamate (GLU) co-release. Such DA-GLU neurons, molecularly defined by co-localization of Tyrosine hydroxylase (Th) and Vesicular glutamate transporter 2 (Vglut2), are primarily present in the medial VTA, send projections to the medial nucleus accumbens shell, and mediate behavioral response to psychostimulants. A recent study identified unexpected VTA expression of the TrpV1 gene, encoding the Transient Receptor Potential cation channel V1 (TRPV1, aka capsaicin receptor), known for its role in peripheral GLU neurons. We hypothesized that a TrpV1+ identity defines a molecularly distinct subpopulation of DA-GLU VTA neurons. To explore anatomical and functional properties, histological analyses and Cre-driven mouse genetics were employed. TrpV1 mRNA was most strongly detected at the perinatal stage forming a band of scattered neurons throughout the medial VTA, stretching into the posterior hypothalamus. In the VTA, TrpV1 co-localized substantially with markers representative of a combined DA-GLU phenotype (Th, Vglut2, Vesicular monoamine transporter 2 (Vmat2)). These TrpV1+/Th+/Vglut2+/Vmat2+ neurons were primarily localized in the interfascicular (IF) and paranigral (PN) subnuclei, forming a molecularly and anatomically distinct VTA subpopulation. To investigate the potential impact of DA transmission exerted by these neurons, a TrpV1-Cre-driven strategy targeting the Vmat2 gene was used, generating a new conditional knockout (cKO) mouse line (TrpV1Cre;Vmat2flox/flox). cKO mice were largely indistinguishable from littermate control mice. However, pharmacological challenge with the psychostimulant amphetamine revealed a significantly altered locomotor response. The acute effect of the drug was accentuated above control levels, suggesting super-sensitivity in the drug-naïve state resembling a “pre-sensitized” phenotype. However, no progressive increase with repeated injections was observed. This study identifies a distinct TrpV1+ VTA subpopulation as a critical modulatory component in responsiveness to amphetamine. Moreover, expression of TrpV1 in selected VTA neurons opens up for new possibilities in pharmacological intervention.